Prevalence of rotavirus in a semi urban area - Reddy A., Naveen Kumar; Yamasani, Nageswara Reddy (International Journal of Contemporary Pediatrics, 2016)
Background: Rotavirus is one of the leading causes of mortality among children with acute watery diarrhea. There is an urgent need to estimate the prevalence of this infection in different localities so that proper measures can be taken to curb the infection especially with the advent of the new oral live vaccines. Methods: 246 children belonging to the age of 5 years admitted to our hospital with acute watery diarrhea were included into the study. General demographic details were taken for all the patients with thorough clinical and physical examination. History regarding the number of stools per day, consistency, types of feeds like exclusive breast feeds, exclusive top feeds or both was noted. Rotavirus was detected on stool samples by ELISA method. Results: 36.2% of the total patients with diarrhea were positive for rota viral infection, and 74.2% of the rotavirus burdens were seen below the 2 year age group. 12.4% of the children infected with rotavirus were exclusively on breast feed, while 32.6% were exclusively on top feed. 55.1% of them were on both mixed (breast and top) feed. The most common comorbidity observed along with rotavirus infection was dehydration, followed by vomiting, lethargy and fever. Conclusions: There is a significant prevalence of rotavirus in our geographical area as well. Since the rotavirus infection is a public health problem, proper surveillance is to be done to find out the exact prevalence of the disease in a hospital among the admitted children as well as those in the community, so as to actively take protective measures.